Analysis of Manheim Peritonitis Index Scoring in Predicting Outcome in Patients with Perforation Peritonitis: Manheim Peritonitis Index Scoring in Patients with Perforation Peritonitis - Furrukh Aftab, Muhammad; Niaz, Khurram; Talha Bukhari, Muhammad; Kareem, Talha; Munim Akram, Abdul; Ali Rabbani, Muhammad (Pakistan Journal of Health Sciences, 2023)
Scoring systems are essential to calibrate the severity of abdominal sepsis for adequate management. Disease specific scoring system based on easy to handle clinical parameters can help the cause. Objective: To study the role of Manheim peritonitis index scoring in predicting outcome and prognosis in patients with perforation peritonitis. Methods: This prospective study was carried out in Surgical Unit 1, Nishtar Hospital, Multan from 20th of August 2019 to 31st of December, 2019. It includes both sexes aged 20 years and above diagnosed at laparotomy after confirmation of peritonitis due to perforated viscus regardless of the etiology. Data were analyzed using SPSS version 19.0 Software. The outcome (death vs discharge) was compared separately to different predictors using Chi-square test. Fischer Exact test was used where assumptions of Chi-square were not met. Results: Advance age, female gender, colonic perforation, organ failure and fecal contamination were associated with high mortality. The mean MPI Score was 25.06 ± 4.96. The lowest score was 16 and the highest was 37. Overall, the in-hospital mortality rate was 14.3% in patients with MPI ≥26 compared to 6.4% in patients with MPI <26, implying over a twofold higher risk in the former group. For a score of 26 or greater as a predictor of mortality, the sensitivity was 75.0%, specificity was 38.2% at an accuracy of 94%. Conclusion: MPI enables us to categorize patients into different groups so as to tailor management according to individual needs